The Innovative Methods of Teaching Ashtang Yoga for School Children Snake and Ladders Game - Manish Kumar; Gowda, Paran; Panwar, Poonam (JOURNAL OF INDIAN EDUCATION, 2020)
Yoga is being widely practiced as an activity in schools nowadays; however children may not be aware of eight folds of ‘Patanjali Ashtang Yoga’. It is need of the hour to teach ‘Patanjali’s Ashtang Yoga’ essence to the children in a simplified and interesting manner. In this study, the nectar of Patanjali aphorisms has been designed and developed as Snakes and Ladders Boards Game and its efficacy was tested among sixty students of standard 4 to 11 at a shelter home in Kurukshetra, Haryana. The study found that the Snake and Ladder Board Game is effective in providing value education on the principles of eight folds of Ashtang Yoga at a young age. It also found that children may understand how good deeds lead them to rise; bad deeds worsen to falls and emphasise the underlying impact of positive and negative forces.